Reformulasi Hubungan Warga Dan Pemerintah Dalam Penanganan Stunting Di Kabupaten Kulon Progo - Fernanda, Lean (Journal of Society Bridge, 2024)
Reformulating the relationship between citizens and government in handling stunting is an important step to improve the effectiveness of stunting interventions. Indonesia, as a country with a large population, still faces a high prevalence of stunting to date, which reflects chronic nutritional problems and challenges in fulfilling children's human rights to adequate nutrition. Specifically in the handling of stunting in Kulon Progo Regency, the prevalence of stunting among children under five in 2022 reached 15.8%, higher than the national target of 14%, making it a region with a significant stunting problem in DIY Province. Factors contributing to stunting in this region include nutritional problems, lack of knowledge and awareness about the importance of nutrition, and poor environmental and sanitation conditions. A holistic approach involving various stakeholders is needed to address this problem. The research method used in this research a systematic review method based on the Preferred Reporting Items for Systematic Reviews and Meta Analyzes (PRISMA). The research also adopted a participatory approach to understand the social dynamics and specific needs of local communities. The research highlights the importance of active participation from local governments, non-governmental organizations, the private sector, and communities in well-coordinated intervention programs. Increased access to health services, nutrition education, and improved sanitation infrastructure are expected to help reduce stunting rates and improve the welfare of children in Kulon Progo Regency. The results of this study are expected to serve as a reference for policy makers and program implementers in formulating effective strategies to address stunting, as well as strengthening collaboration between government and citizens in sustainable health development efforts.